Antiatherogenic effect of simvastatin is not due to decrease of LDL cholesterol in ovariectomized golden Syrian hamster - Piťha, Jan; Bobková, Dagmar; Kovář, Jan; Havlíčková, Jana; Poledne, Rudolf (Physiological research, 2010)
The changes of the composition of blood lipoproteins caused by menopause could also change the effect of hypolipidemic therapy. Using an experimental model we studied the changes of serum lipids and the effect of immediate or delayed treatment with simvastatin on atherosclerosis after surgical menopause. Female golden Syrian hamster aged 6 months were fed hypercholesterolemic diet during the whole study. Atherosclerotic changes in thoracic and abdominal aortas were assessed by stereomicroscopic method after 12 weeks. Four experimental groups were studied: sham-operated animals (n=5), ovariectomized animals (n=9), ovariectomized animals treated for 12 weeks (n=10), and ovariectomized animals treated 4 weeks after ovariectomy for 8 weeks (n=9). The dose of simvastatin was 10 mg/kg of body weight. After 12 weeks, ovariectomized animals had tenfold higher concentration of triglycerides in LDL fraction and significantly higher prevalence of atherosclerosis than animals without ovariectomy. Treatment with simvastatin substantially decreased the prevalence of atherosclerotic changes, but otherwise did not change individual serum lipids including LDL cholesterol. However, it improved proportions of pro- and antiatherogenic serum lipids mainly by the increase of HDL cholesterol. The timing of simvastatin treatment had no significant effect on atherosclerotic changes or lipid parameters. Simvastatin treatment partly prevented atherosclerotic changes induced by ovariectomy. This effect was not mediated by decrease of LDL cholesterol, but by increase in HDL cholesterol.
Keywords: nemoci aorty; Simvastatin; modely nemocí na zvířatech; Ovariectomy; Cholesterol, LDL; biologické markery; HDL-cholesterol; Biomarkers; LDL-cholesterol; Cholesterol, HDL; Drug Administration Schedule; Mesocricetus; ateroskleróza; Hydroxymethylglutaryl-CoA Reductase Inhibitors; statiny; křeček rodu Mesocricetus; simvastatin; Aorta, Thoracic; aorta abdominalis; triglyceridy; Aortic Diseases; Time Factors; Cricetinae; aorta thoracica; Animals; ženské pohlaví; Atherosclerosis; ovarektomie; zvířata; Aorta, Abdominal; časové faktory; Disease Models, Animal; Financing, Organized; rozvrh dávkování léků; lipoproteiny LDL; Female; financování organizované; Lipoproteins, LDL; křečci praví; Triglycerides